PENGARUH KARAKTERISTIK PIMPINAN DAN INOVASI PRODUK BARU TERHADAP KINERJA PERUSAHAAN UNTUK MENCAPAI KEUNGGULAN BERSAING BERKELANJUTAN - Ratna Kusumawati (AKSES: Jurnal Ekonomi dan Bisnis, 2010)
Intense competition requires companies to further improve corporate performance through a leadership role in motivating subordinates to be able to remove his ideas to create new products that the company expected the company can always have a sustainable competitive advantage to remain competitive with rival companies. The results of this study indicate that: 1) there is a positive influence to the performance characteristics of the leadership of the company, 2) new product innovation has positive and significant impact on company performance, 3) new product innovation has positive and significant impact on sustainable competitive advantage, 4) performance of the company has positive of sustainable competitive advantage.Keywords: characteristics of leadership, new product innovation, company performance, sustainable competitive advantage.